Premature ejaculation – definition, classification and therapy. Part I - Gałecki, Piotr; Depko, Andrzej; Bobińska, Kinga; Mossakowska-Wójcik, Joanna; Ciosek, Małgorzata; Mazur, Joanna; Talarowska, Monika (Current Problems of Psychiatry, 2011)
Premature ejaculation (PE) and erectile dysfunction (ED, impotence) are the two main complaints in male sexual medicine. It can affect men at all ages and has a serious impact on the quality of life for men and their partners. Although PE is a very common male sexual dysfunction, it is poorly understood. Patients are often unwilling to discuss their symptoms and many physicians do not know about effective treatments. Therapy should involve the man and his partner (mainly psychotherapy and sexual education). The primary aims of therapy are for the man to extend the intravaginal ejaculation latency time (IELT),to regain a sense of control over his ejaculation time and for him and his partner to feel satisfaction with sexual intercourse. The most effective therapies for PE are: tricyclic antidepressants, certain selective serotonin reuptake inhibitors (SSRI, mainly dapoxetine), serotonin antagonist and reuptake inhibitor (SARI) and phosphodiesterase type 5 inhibitors (PDE-5), given on a daily basis or “on demand” before sexual activity. Topical anaesthetics have also been shown to be effective. The aim of the study is to describe the prevalence, the diagnosis and the classification of the PE. In the second part the main issues which are connected with biological therapy (pharmacotherapy) of the PE were described.